Menciptakan Lampu Hias Dinding Ukir dengan Berbagai Ornamen Karo - Debi Yaini Br Sembiring; Misgia Misgia; Raden Burhan (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study aims to create a carved wall decorative lamp that highlights and introduces the rich traditional ornaments of the Karo ethnic group. The creation process includes the stages of form exploration, design planning, and piercing carving techniques using materials such as mahogany wood, jelutung, and bamboo. The Karo ornamental motifs used in this creation include the motifs of Palm Manggis, Lukisen Umang, Pengeret-ret, Pendamaiken, Desa Siwaluh, Pucuk Marebung, Bungga Gundur, Teger Tudung, Sisik Kaperas, Lukisen Kurung Tendi, Kaba-kaba, Pucuk Tengiang, Lukisen Suki, Tutup Dadu, Cimba Lau, Embun Sikawiten, Bindu Mateguh, and Tapak Raja Suliaman, which were selected for their strong aesthetic values and philosophical meanings. This work serves not only as a source of decorative lighting but also as a medium for preserving Karo cultural heritage. The result shows that the combination of function and traditional values can produce applied art that is both aesthetic and meaningful.